Hubungan Preeklamsia Dengan Kejadian Persalinan Preterm di Rumah Sakit Umum Kabupaten Tangerang - Nurhayati Nurhayati (Quality : Jurnal Kesehatan, 2018)
The incidence of preterm birth in developing countries is (5% -7%) per 1000 live births and the prevalence of preterm births in Indonesia is (18.5%). Preeclampsia is one of the causes of high maternal and fetal morbidity and mortality rates in Indonesia. Preeclampsia generally occurs after 20 weeks of pregnancy. Objective: To determine the relationship of preeclampsia to the incidence of preterm labor and other factors affecting preterm birth. Method: An observational study with a case control design at the Tangerang General Hospital. The total cases were 90 people (mothers gave birth to a single baby at 20-36 weeks 'gestation) and there were 100 controls (mothers gave birth to a single baby at â‰¥37 weeks' gestation). Univariable, bivariable analysis with Chi Square statistical test at significance level p <0.05, 95% CI. Multivariable analysis with logistic regression models was used to estimate the odds ratio and 95% CI risk of preeclampsia / eclampsia in the incidence of preterm birth. Results: Mothers with mild preeclampsia and preeclampsia had a risk of preterm birth (OR: 3.85; 95% CI: 2.06-6.50) compared to non-preeclampsia. Other factors that influence the incidence of preterm birth are a history of preterm and antenatal care. Conclusion: Mothers with preeclampsia are at risk for preterm birth. The incidence of preterm birth was also influenced by a history of preterm and antenatal care.